Poland’s Foreign Policy Mechanisms: Legal Framework and Policy Analysis - Yana A. Vorozheina (Baltic Region, 2017)
This article describes the features of Poland’s foreign policy. Special attention is paid to the foreign policy mandate of the president, government, and minister of foreign affairs and the procedure for devising Poland’s foreign policy strategy. Another focus is the contribution of local government to Poland’s foreign policy. The author describes the features of Poland’s foreign policy mechanism and emphasises its potential instability associated with a multi-tier decision-making procedure and blurred boundaries between foreign policy mandates conferred by the Constitution upon the government and president. The latter creates a potential for institutional conflict. It is stressed that the efficiency of Poland’s foreign policy mechanism is strongly affected by the relations between the government and the president and requires consensus on all major foreign policy issues. The author emphasises the effect of the domestic policy situation on Polish foreign policy mechanism and, as a result, the Republic’s stance in the international arena.